2016
DOI: 10.1016/j.radcr.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical case report: Sclerosing hemangioma of the liver, a rare but great mimicker

Abstract: Atypical hemangioma (including sclerosing and/or hyalinizing hemangioma) of the liver is a rare variant of hepatic hemangioma, which is the most common benign hepatic tumor. Atypical hemangioma can be indistinguishable from malignancy, primary, or metastatic, based on imaging characteristics. We describe a case of a 70-year-old man with weight loss, occasional bloody stool, change in caliber of stool, and laboratory abnormalities who was found to have multiple hepatic lesions concerning for metastases. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In contrast however, they could also show geographic pattern, capsular retraction, and loss of previously seen regions of enhancement [ 9 ]. The radiological features of sclerosing hemangiomas revealed by dynamic CT and MRI are similar to those of hepatic malignancies making the diagnosis highly challenging based on imaging alone [ 10 ]. It is hypothesized, however, that the use of [18F]-fluorodeoxyglucose positron emission tomography (FDG-PET) could be helpful in the preoperative diagnosis to distinguish benign sclerosed hemangioma from a malignant tumor such as intrahepatic cholangiocarcinoma or metastatic liver cancers [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast however, they could also show geographic pattern, capsular retraction, and loss of previously seen regions of enhancement [ 9 ]. The radiological features of sclerosing hemangiomas revealed by dynamic CT and MRI are similar to those of hepatic malignancies making the diagnosis highly challenging based on imaging alone [ 10 ]. It is hypothesized, however, that the use of [18F]-fluorodeoxyglucose positron emission tomography (FDG-PET) could be helpful in the preoperative diagnosis to distinguish benign sclerosed hemangioma from a malignant tumor such as intrahepatic cholangiocarcinoma or metastatic liver cancers [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic sclerosing hemangiomas are caused by degenerative changes such as thrombus formation, necrosis, and scar formation within liver cavernous hemangioma, and such variations in the pathological characteristics make precise radiological diagnosis very difficult 5. Sclerosing hemangioma is frequently misdiagnosed as an intrahepatic malignancy or metastatic lesions, for which a hepatectomy is performed 58. In the present case, the preoperative contrast MRI captured a large hepatic cavernous hemangioma and the sclerosing hemangioma could not be detected, because most of the tumor was composed of cavernous hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the tumors reported previously were resected due to preoperative misdiagnosis as hepatic malignancies. Behbahani et al have shown that knowledge of the appearance of atypical hemangioma and its inclusion in the differential diagnosis of hepatic lesions can alter patient management, being an important aspect to consider before invasive therapies are planned [ 9 ]. On the other hand, in fine-needle aspirates, the smears tend to be hemorrhagic, and sometimes only blood is aspirated.…”
Section: Discussionmentioning
confidence: 99%